2005
DOI: 10.13001/1081-3810.1175
|View full text |Cite
|
Sign up to set email alerts
|

Graphs whose minimal rank is two: The finite fields case

Abstract: Abstract. Let F be a finite field, G = (V, E) be an undirected graph on n vertices, and let S (F, G) be the set of all symmetric n × n matrices over F whose nonzero off-diagonal entries occur in exactly the positions corresponding to the edges of G. Let mr(F, G) be the minimum rank of all matrices in S(F, G). If F is a finite field with p t elements, p = 2, it is shown that mr(F, G) ≤ 2 if and only if the complement of G is the join of a complete graph with either the union of at most (p t +1)/2 nonempty comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…At the 2005 Oberwolfach graph theory workshop, Hein van der Holst asked if there are only finitely many k-critical graphs for any k and F . (Barrett, van der Holst, and Loewy [2,1] had recently confirmed this for k ≤ 2 and any F .) When F is finite, we answer this question affirmatively, by providing an upper bound on the size of a k-critical graph.…”
mentioning
confidence: 70%
“…At the 2005 Oberwolfach graph theory workshop, Hein van der Holst asked if there are only finitely many k-critical graphs for any k and F . (Barrett, van der Holst, and Loewy [2,1] had recently confirmed this for k ≤ 2 and any F .) When F is finite, we answer this question affirmatively, by providing an upper bound on the size of a k-critical graph.…”
mentioning
confidence: 70%
“…Barrett, van der Holst, and Loewy also have characterizations for infinite fields of characteristic two [5] and for finite fields [6]. These results provide tools that may allow characterizing minimum rank at most two over finite fields or fields of characteristic two.…”
mentioning
confidence: 89%
“…For example, Johnson and Leal Duarte [10] showed that the minimum rank of a tree equals the minimum number of disjoint paths needed to cover all vertices of the tree. Barrett, Loewy, and van der Holst [2,3] gave for any field F a combinatorial characterization of the class of graphs G with mr(G; F) ≤ 2. Also for the class of complement of trees, the minimum rank has been determined [8].…”
Section: Introductionmentioning
confidence: 99%